Endothelial function in men with type 2 diabetes without clinical signs of cardiovascular disease - Irina Alexandrovna Khripun; Sergey Vladislavovich Vorobyev; Maxim Nikolaevich Morgunov; Michail Iosifovich Kogan (Сахарный диабет)
Type 2 diabetes mellitus (T2DM) increases the risk of cardiovascular disease that is based on endothelial dysfunction (ED). Currently, conventional diagnostic methods are unreliable, especially at early stages of disease.Aims. The aim of this work was to assess endothelial function in men with T2DM without clinical signs of cardiovascular disease.Materials and methods. The study included 100 patients (mean age, 54.3 ± 5.3 years) with a T2DM duration of less than 10 years and without signs of cardiovascular disease. The patients were divided into two groups: group 1 consisted of 60 patients with a T2DM duration of less than five years. Group 2 included 40 men with a history of diabetes between 5 and 10 years. Endothelial function was assessed by the levels of nitric oxide (NO), endothelial NO synthase type 3 (eNOS3), ICAM-1, VCAM-1, E-selectin, P-selectin, resistin and C-reactive protein and the arterial vasoreactivity of the brachial artery (BA) using the D. Celermajer method.Results. Results revealed decreases in levels of both eNOS3 by 2.5 fold (P = 0.0005) and NO by 1.9 fold (P = 0.043) in group 2 patients, compared to those in group 1 patients. When the duration of diabetes was greater than five years, levels of VCAM-1, resistin and C-reactive protein increased by 12.1% (P = 0.048), 62% (P = 0.01) and 45.6%, respectively. Additionally, the time until maximal BA vasodilatation during reactive hyperemia was observed to be higher in group 2 [105 (90; 180) seconds] than those in group 1 [90 (60; 120) seconds].Conclusions. Biochemical and imaging signs of ED begin to appear in the first five years of T2DM, long before clinical manifestations. The earliest symptoms are decreases in eNOS3 and NO levels, increases in VCAM-1 and resistin concentrations and increased time until maximal BA vasodilatation during reactive hyperemia.